(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Chitosan beads demonstrate good adsorption capacity in wastewater treatment. The ease with which the chitosan beads separate from the effluent and the possibilities of sorbent regeneration have made chitosan beads a more prominent form for biosorption. However, chitosan beads form gels at pHs below 5.5, which makes them unsuitable to be employed in treatment process. Bifunctional agents are introduced to increase the integrity of the beads by crosslinking chitosan. Crosslinked chitosan beads exhibit different adsorption capacities for distinct types and categories of dyestuffs. In this study, the removal of Direct Red 80 (DR80), Reactive Yellow 25 (RY25) and Acid Blue 25 (AB25) dyes by chitosan-based beads has been investigated. Variation in pH and temperature, effect of crosslinking and encapsulation of bacteria Lactobacillus casei are evaluated for their influence on the adsorption behaviour. Zeta potential and structural characterization of the synthesized chitosan beads are performed. Adsorption equilibriums are achieved in about five hours. The chitosan beads are crosslinked with glutaraldehyde to avoid their dissolution at pH 2 and the beads achieve complete removal of the three dyes within one hour. Temperature increase induces a positive effect on the adsorption of DR80, but an insignificant effect on that of RY25 and negative effect on AB25. Adsorption with the crosslinked beads at pH 5.5 and 37^°C promotes the removal of RY25 and AB25 by at least two folds more than that by non-crosslinked chitosan beads, but is found to be less effective on DR80. Significant increase of DR80 adsorption is achieved by adopting the crosslinked-bacteria-encapsulated chitosan beads while the effect on AB25 and RY25 are similar when compared to blank crosslinked beads. Langmuir and Freundlich isotherms fit the experimental data and the pseudo-second order equation agrees very well with the kinetic data.